Teacher’s role in adaptation of musical art students to the study in higher educational establishment - Дорош, Т. Л. (Scientific notes of the pedagogical department, 2018)
In the article the special role is given to a teacher, who helps a musical art student to adapt quickly to the modern conditions in higher educational establishment. Students, who enter higher educational establishments, get into a new environment, where new relations are established, the new social circle is created, the usual rhythm of their life changes. The adaptation to these changes, the readiness to the active collaboration with teaching staff and students’ collectives, participating in class and extracurricular activities (a concert performance, creative summary, competitions) solving problematic issues is the key to successful adaptation. The author focused on the main stages of process of adaptation, each of which has its own features and provides for a preparatory stage, readiness for collective cooperation and organized self-study and analytical aspect. Furthermore, the concrete examples of adaptation of musical art students in «Kharkiv Humanitarian-Pedagogical Academy» of Kharkiv Regional Council are provided. The adaptation of musical art students occurs during the preparation for concert performances, competitions, scientific activity, creative search and research work. In concerts special attention is paid to bright performance, technique, artistic embodiment, band performance, intonation, composition unity, high-quality musical play. In the research the adaptation is examined not only as the students’ adaptation to the new system of studying for them, but also their activity in new conditions and situations, as a result the positive attitude occurs towards classes, the own behavior is regulated and controlled, new knowledge is acquired also students broaden their horizons. The attention is drawn to the fact that not only a student has to adapt to music lessons, the requirements, but also a teacher has to adapt to a new student. Furthermore the teacher has to make every effort to find out the reasons that block the students’ development, eliminate negative effects and strengthen that contributes to their successful development. Researching this problem will allow a teacher to be more educated, well-informed with deep general scientific, musical knowledge, to give the knowledge to the students and, accordingly, to organize their scientific, creative, cognitive and working activity.